Estudo da modificação do ângulo do conjunto cilindro-pistão em motores de combustão interna - Gay, Matheus de Andrade [UNESP] (2012)
The aim of this study is to present those who are interested in mechanical engineering, specifically automotive engineering some ideas for improvements to the current concept of internal combustion engines. It is not intenden to change totally the design of the engine known today, but to exame the feasibility of reducing a small waste generated with the current positioning of the cylinder-piston assembly. The proposal solution consists in modifying the tilt cylinder-piston assembly in the angle between the rod and the cylinder axis. This inclination causes all the force generated in the combustion process within the cylinder is delivered to the rod.Delivery force is the made in the rod longitudinal direction and not on the axis of the cylinder, preventing the occurrence of a breakdown of the force generated in the combustion process. After analyzing the idea of repositioning the piston-cylinder assemble, it is concluded that the change has a positive result in the process of harnessing the power generated in the com bustion, but its not feasible due implementation to low gain presented in this study